Effect of Rates and Methods of Nitrogen Application on the Yield and Yield Attributes of Rainfed Bajra HB3 Grown in The Arid Zone - Singh, R P; Daulay, H S; Singh, K C; Gupta, B S (Annals of Arid Zone, 2016)
Responqe of rainfe bajra HR3 to four levels of nitrogen (0,40, 80, and 120 kg N/ha) and the efficacy of different methods of nitrogen application (Broadcast and incorporated, placement 10 cm deep, placement 5 cm deep and 5 cm to the sides, half soil + half foliar, threefourths soil + one-fourth foliar, half placement + half topdressing) was studied for two consecutive years. 1971 and 1972, at the research farm of the Central Arid Zone Research Institute, Jodhpur. Application of 40 kg N/ha either broadcast and incroporated or placed 10 cm deep at the time of sowing resulted in increased grain yields of the order of 44 to 96% over the unfertilised control, the response being 10.0, 5.3 and 3.4 kg grains lkg N to 40, 80 and 120 kg N/ha. respectively. Response beyond 40 kg N/ha was uneconomical. The optimum dose of fertiliser nitrogen for rainfed bajra HB3 at the current price of nitrogen IRs 3.801kg) and current market price of bajra (Rs 100/q) worked out to 47 to 55 kg/ha. Half soil and half top dressing method of nitrogen application proved most efficacious and gave the maximum net returns (Rs 627lha). It is more economical and safe to apply half the dose of nitrogen (20 kg N/ha) through placement 10 cm deep at the time of sowing and the remaining half (20 kg N/ha) as top dressing 35 to 40 days after sowing.